Rethinking the philosophical and theoretical foundations of organizational neuroscience: A critical realist alternative - Healey, Mark P; Hodgkinson, Gerard P (Human relations (New York), 2014)
Stimulated by the growing use of brain imaging and related neurophysiological techniques in psychology and economics, scholars have begun to debate the implications of neuroscience for management and organization studies (MOS). Currently, this debate is polarizing scholarly opinion. At one extreme, advocates are calling for a new neuroscience of organizations, which they claim will revolutionize understanding of a wide range of key processes, with significant implications for management practice. At the other extreme, detractors are decrying the relevance of neuroscience for MOS, primarily on philosophical and ethical grounds. The present article progresses this debate by outlining an intermediate, critical realist position, in which the insights of social neuroscience are one of a number of convergent building blocks that together point toward the need for a more embodied and socially situated view of cognition in management and organizations.